That’s a Rap: Increasing Engagement with Rap Music Performance by Virtual Agents - Olafsson, Stefan; Kimani, Everlyne; Asadi, Reza; Bickmore, Timothy (Intelligent Virtual Agents, 2017)
Many applications of virtual agents, including those in healthcare and education, require engaging users in dozens or hundreds of interactions over long periods of time. In this effort, we are developing conversational agents to engage young adults in longitudinal lifestyle health behavior change interventions. Hip-hop and rap are one of the most popular genres of music among our stakeholders, and we are exploring rap as an engagement mechanism and communication channel in our agent-based interventions. We describe a method for integrating rap into a counseling dialog by a conversational agent, including the acoustic manipulation of synthetic speech and accompanying character dance animation. We demonstrate in a within-subjects study that the participants who like rap music preferred the rapping character significantly more than an equivalent agent that does not rap in its dialog, based on both self-report and behavioral measures. Participants also found the rapping agent significantly more engaging than the non-rapping one.